2021
DOI: 10.1177/25158414211030427
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of lacrimal probing surgery as the first option in the treatment of congenital dacryocystocele

Abstract: Purpose: To determine the demographic and clinical characteristics of newborn patients who underwent lacrimal probing surgical intervention with or without the marsupialization of intranasal cysts as the primary management for dacryocystocele treatment. Methods: Data from the medical charts of 350 infants who underwent lacrimal probing surgery due to nasolacrimal duct obstruction were reviewed retrospectively. Ten newborn patients with a naive diagnosis of congenital dacryocystocele were included in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…After confirming the diagnosis by lacrimal excretion test and radiological examination, the outcome of appropriate surgical treatment should be successful. [10][11][12] In this case, we found that the patient eventually underwent the "right eye and nose endoscopy" under the nasal endoscope. The symptoms of tears disappeared the next day after the operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After confirming the diagnosis by lacrimal excretion test and radiological examination, the outcome of appropriate surgical treatment should be successful. [10][11][12] In this case, we found that the patient eventually underwent the "right eye and nose endoscopy" under the nasal endoscope. The symptoms of tears disappeared the next day after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…After confirming the diagnosis by lacrimal excretion test and radiological examination, the outcome of appropriate surgical treatment should be successful. 10 - 12 …”
Section: Discussionmentioning
confidence: 99%
“…Congenital dacryocyst is a cyan cystic mass in the inner canthus of newborns, and is caused by obstruction at both ends of the diversion channel [ 6 ]. Some study reported that in children, nearly 60% of patients with congenital dacryocyst eventually develop a peri-dacryocyst infection [ 7 , 8 ]. Dacryocystitis is mainly caused by Gram-positive cocci, especially Streptococcus pneumoniae ; due to the misuse of anti-Gram-positive cocci antibiotics, Gram-negative Enterobacteriaceae have risen in the proportion of dacryocystitis pathogens [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Congenital dacryocyst is a cyan cystic mass in the inner canthus of newborns, and is caused by obstruction at both ends of the diversion channel, leading to dilation of the lacrimal sac, enlargement of the nasolacrimal duct, and the formation of a cystic mass in the nose 4 . Congenital dacryocystitis often develops into dacryocystitis or orbital cytitis, which can be life threatening 5 .Some study reported that in children, nearly 60% of patients with congenital dacryocyst eventually develop a peri-dacryocyst infection 6 . However, there is no data about the epidemiology of pediatric dacryocystitis and the distribution of dacryocystitis pathogens.…”
Section: Introductionmentioning
confidence: 99%